2021
DOI: 10.1111/acem.14377
|View full text |Cite
|
Sign up to set email alerts
|

Integration of social media with targeted emails and in‐person outreach for exception from informed consent community consultation

Abstract: Background: Exception from informed consent (EFIC) enables the enrollment of research subjects with emergent conditions to clinical trials without prior consent. EFIC study approval requires community consultation and public disclosure. We hypothesized that the integration of social media with targeted emails and in-person outreach is an effective community consultation strategy. Methods:We utilized social media with targeted emails and in-person outreach for the community consultation of the ACCESS cardiac ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(30 reference statements)
0
4
0
Order By: Relevance
“… 15 Community meetings and individual interviews are generally associated with higher rates of acceptance than remote surveys, 15 but may include a different demographic group relative to age, sex, educational level, and familiarity with electronic technology. 8 Our PROTECT in-patient interviews yielded lower acceptance rates and higher opt-out rates than our remote surveys, perhaps reflecting hospitalization for a medical problem or demographic differences between the groups. Hsu et al found a similar lower acceptance rate with individuals in cardiology clinic waiting rooms before the pandemic compared to surveys returned electronically.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“… 15 Community meetings and individual interviews are generally associated with higher rates of acceptance than remote surveys, 15 but may include a different demographic group relative to age, sex, educational level, and familiarity with electronic technology. 8 Our PROTECT in-patient interviews yielded lower acceptance rates and higher opt-out rates than our remote surveys, perhaps reflecting hospitalization for a medical problem or demographic differences between the groups. Hsu et al found a similar lower acceptance rate with individuals in cardiology clinic waiting rooms before the pandemic compared to surveys returned electronically.…”
Section: Discussionmentioning
confidence: 66%
“…Hsu et al found a similar lower acceptance rate with individuals in cardiology clinic waiting rooms before the pandemic compared to surveys returned electronically. 8 Though commonly reported as part of the community consultation process, closed-ended surveys designed to provide a percent “acceptance” may fail to capture and explore distinct views of sub-groups within the population; opportunities for open-ended comments and two-way communication should also be included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, social media-based CC campaigns have become more commonplace, 2,6,8,9 not only for trauma trials but also other conditions. These campaigns can take advantage of the interactive components of the ability of social media to: (1) provide information to a large number of individuals, provide an efficient mechanism for obtaining feedback; (2) accomplish outreach including accruing granular metrics about the search and review functions of viewers (e.g., number of people reached, time individuals spent reviewing various aspects of clinical trial information); and (3) seek feedback through online surveys (both linked and unlinked to social media).…”
Section: How Can Social Media Be Leveraged To Facilitate Cc?mentioning
confidence: 99%